Mobile Computing: Current Trends, Security Issues, and Future Directions - Sapandeep Kaur Dhillon; Harjit Kaur (International Journal of Wireless Security and Networks, 2023)
Mobile computing is a rapidly emerging technology that is revolutionizing various sectors such as education, healthcare, tourism, transportation, manufacturing, banking, insurance, and hospitality. It is widely recognized as a potent computational tool that possesses the capability to profoundly influence society. By providing a mobile user with access to a wide range of information sources, the ability to exchange electronic messages, real-time interaction with other users, and the utilization of remote computing resources, mobile computing offers a versatile and dynamic interface to services. This paper aims to present a conceptual overview of mobile computing, addressing its security concerns and future prospects. Furthermore, it will provide a brief discussion on current trends and ongoing research projects in the field of mobile computing worldwide.
Keywords: 5G networks; Applications; Augmented reality; Mobile computing; Security Issues; artificial intelligence; current trends; future directions; wireless networks